Clinical And Hematological Profile Of Patients With Dengue Fever At A Tertiary Care Hospital – An Observational Study - Parmar, Manish Prakashbhai (Journal of Neonatal Surgery, 2025)
Background: Dengue fever is a mosquito-borne tropical disease caused by the dengue virus. Symptoms typically begin 3-14 days after infection. This may include a high fever, headache, vomiting, muscle and joint pains, and a characteristic skin rash. Aim: Objective of this is to evaluate the clinical and hematological characteristics of dengue patients in a tertiary care hospital. Materials and methods: A cross-sectional study was carried out among patients with positive dengue serology results for NS1, IgM, and IgG. A total of 200 dengue cases that fulfilled the inclusion criteria were enrolled in the study. Clinical examination findings were recorded, hematological and biochemical parameters tests were done Results: In our study, the incidence of dengue fever common in males (56%) compared to females (44%). Majority of patients (38%) were in the age group 21-40 years. Out of total 70% patients were diagnosed to have DF, 24% DHF and 6% patients were diagnosed to have DSS based on WHO criteria. NS1 were positive in 64% of patients. Common clinical manifestations were fever (100%) followed by headache (80%), joint pain (65%), myalgia (53%), vomiting (43%), and retro-orbital pain (33%). Hemetemesis/Malena (20%), petechiae (15%), epitasis (7%) and bleeding gums (6%) was the common bleeding manifestations. Leucopenia, thrombocytopenia and high hematocrit were the common hematological parameters in dengue. Conclusion: Most common clinical presentation of Dengue fever is of fever. The most common laboratory abnormalities are of an increase in hematocrit, low total leucocyte count and low platelet count. Early diagnosis and prompt management of dengue can prevent complications